ANALISIS TRANSFORMASI DIGITAL DALAM KEWIRAUSAHAAN SYARIAH: EKSPLORASI MENDALAM ATAS PELUANG DAN TANTANGAN DALAM EKONOMI SYARIAH PADA MAHASISWA UIN RADEN FATAH PALEMBANG - Nova Adrian; Aqila Mahira; Riris Ariska; Ancika Dilza Ramadhani; Ana Muasaroh (CV. Cendikiawan Muda Sriwijaya, 2026)
This study aims to analyze digital transformation in sharia entrepreneurship among students of UIN Raden Fatah Palembang, particularly regarding the opportunities and challenges in developing digital-based businesses. This research employed a descriptive qualitative approach with data collection techniques through interviews, observation, and documentation. The results indicate that digital transformation plays an important role in supporting students’ entrepreneurial activities through the utilization of social media, marketplaces, and digital payment systems. Digital technology helps expand market reach, improve communication with consumers, and facilitate business transactions more effectively and efficiently. In addition, digital literacy influences students’ ability to manage and develop digital businesses. The study also reveals that students strive to implement sharia principles such as honesty, transparency, and fairness in digital business activities. However, increasingly competitive digital business competition remains a challenge in maintaining consistency in sharia business ethics. Therefore, improving digital literacy and understanding sharia business ethics are important factors in supporting the sustainability of digital sharia entrepreneurship among students.